A prospective phase II study of prostate-specific antigen-guided salvage radiotherapy and 68Ga-PSMA-PET for biochemical relapse after radical prostatectomy – The PROPER 1 trial - Adalsteinn Gunnlaugsson; Vilberg Johannesson; Elinore Wieslander; Eva Brun; Ulrika Bitzén; Olof Ståhl; Ola Bratt; Göran Ahlgren; Tomas Ohlsson; Elisabeth Kjellén; Per Nilsson (Clinical and Translational Radiation Oncology, 2022)
Background and purpose: The treatment of biochemical recurrence (BCR) after prostatectomy is challenging as the site of the recurrence is often undetectable. Our aim was to test a personalised treatment concept for BCR based on PSA kinetics during salvage radiotherapy (SRT) combined with prostate-specific membrane antigen positron emission tomography (PSMA-PET). Materials and methods: This phase II trial included 100 patients with BCR. PSMA-PET was performed at baseline. PSA was measured weekly during SRT. Initially, 70 Gy in 35 fractions was prescribed to the prostate bed. Radiotherapy was adapted after 50 Gy. Non-responders (PSA still ≥ 0.15 ng/mL) received sequential lymph node irradiation with a boost to PSMA-PET positive lesions, while responders (PSA < 0.15 ng/mL) continued SRT as planned. PET-findings were only taken into consideration for treatment planning in case of PSA non-response after 50 Gy. Results: Data from 97 patients were eligible for analysis. Thirty-four patients were classified as responders and 63 as non-responders. PSMA-PET was positive in 3 patients (9%) in the responder group and in 22 (35%) in the non-responder group (p = 0.007). The three-year failure-free survival was 94% for responders and 68% for non-responders (median follow-up 38 months). There were no significant differences in physician-reported urinary and bowel toxicity. Patient-reported diarrhoea at end of SRT was more common among non-responders. Conclusion: This new personalised treatment concept with intensified SRT based on PSA response demonstrated a high tumour control rate in both responders and non-responders. These results suggest a clinically significant effect with moderate side effects in a patient group with otherwise poor prognosis. PSMA-PET added limited value. The treatment approach is now being evaluated in a phase III trial.Clinical trial registration numbers: NCT02699424&ISRCTN45905321.